Engineering Cobalt Phosphide (CoP) Thin Film Catalysts for Enhanced Hydrogen Evolution Activity on Silicon Photocathodes. Issue 4 (8th December 2015) - Hellstern, Thomas R.; Benck, Jesse D.; Kibsgaard, Jakob; Hahn, Christopher; Jaramillo, Thomas F.
Abstract : Transition metal phosphide catalysts have recently emerged as active, earth abundant alternatives to precious metals for the hydrogen evolution reaction in acid. High performance, scalable catalysts are necessary for the successful implementation of photoelectrochemical water splitting devices, which have the potential to generate hydrogen in a sustainable manner. Herein, a general synthetic route is reported to produce transition metal phosphide thin films, which is used to fabricate cobalt phosphide (CoP) catalysts with high average turnover frequency (TOFavg ), 0.48 H2 s −1 and 1.0 H2 s −1 at 100 and 120 mV overpotential, respectively. Furthermore, it is shown that CoP thin films can be applied to silicon photoabsorbers to generate one of the most active precious metal‐free crystalline silicon photocathodes to date, achieving −10 mA cm −2 at +0.345 V vs. reversible hydrogen electrode. The synthesis route presented here provides a platform for both fundamental studies of well‐defined electrocatalysts and the fabrication of high‐performance photoelectrodes. Abstract : Highly active thin films of cobalt phosphide (CoP) are synthesized on silicon to create efficient nonprecious metal photocathodes. These low light absorbing CoP electrocatalysts are ideal for catalytic and protecting layers in photoelectrochemical water splitting devices. The CoP/silicon photoelectrodes exhibit excellent activity and durability and represent continued progress toward cost effective, sustainable solar water splitting.